SARS-COV-2 protein NSP9 promotes cytokine production by targeting TBK1 - Yihua Zhang; Bowen Xin; Yinan Liu; Wenyi Jiang; Wendong Han; Jian Deng; Peihui Wang; Xiaowu Hong; Dapeng Yan (Frontiers in Immunology, 2023)
SARS-COV-2 infection-induced excessive or uncontrolled cytokine storm may cause injury of host tissue or even death. However, the mechanism by which SARS-COV-2 causes the cytokine storm is unknown. Here, we demonstrated that SARS-COV-2 protein NSP9 promoted cytokine production by interacting with and activating TANK-binding kinase-1 (TBK1). With an rVSV-NSP9 virus infection model, we discovered that an NSP9-induced cytokine storm exacerbated tissue damage and death in mice. Mechanistically, NSP9 promoted the K63-linked ubiquitination and phosphorylation of TBK1, which induced the activation and translocation of IRF3, thereby increasing downstream cytokine production. Moreover, the E3 ubiquitin ligase Midline 1 (MID1) facilitated the K48-linked ubiquitination and degradation of NSP9, whereas virus infection inhibited the interaction between MID1 and NSP9, thereby inhibiting NSP9 degradation. Additionally, we identified Lys59 of NSP9 as a critical ubiquitin site involved in the degradation. These findings elucidate a previously unknown mechanism by which a SARS-COV-2 protein promotes cytokine storm and identifies a novel target for COVID-19 treatment.